Деякі умови забезпечення політико-правової реформи в Україні (теоретично-правовий аналіз) - Оніщенко, Н.; Onishchenko, N. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Політико-правові реформи, що відбуваються сьогодні в Україні, з одного боку, характеризуються інтенсивним характером, із другого – потребують виваженого ставлення до них, відповідного забезпечення, без чого їх завершений характер уявляється неможливим. У статті запропоновано аналіз низки факторів та умов, за наявності яких реформи, що проводяться (конституційна, адміністративна, судова тощо), можуть розглядатися як підготовлені в контексті відповідного функціонування економічної системи, гармонізації правової системи, публічності права тощо.Political and legal reforms taking place today in Ukraine, on the one hand, are characterized by intense character, and on the other, they require a balanced approach as well as proper support. Their complete nature is regarded to be impossible without the later elements. The article offers an analysis of a number of factors and conditions under which reforms can be seen as efficient in the context of the proper functioning of the economic system, the harmonization of the legal system, publicity rights, etc. The author came to a conclusion about the necessity to revive the respect to the law, to the rule of law and the supremacy of law, and the principle of legality. The balance of law and economic life can be defined as follows: the law by means of the objective laws of economy tends to restore social and economic justice in society, with the help of the regulatory norms. It is necessary to implement a qualitatively different approach − a civilized society should acquisite not only legal minimum but appropriate level of legal knowledges. Legal editions perform the necessary public functions under the condition when the legal works of the domestic experts are in demand and all the publications are supported by the academic authority of the authors.
Some Conditions Ensuring the Political and Legal Reform in Ukraine (Theoretical and Legal Analysis)
Keywords: умови та фактори проведення реформ; правова система; економічна система; публічність права; правовий оптимізм; наслідки реформування; conditions and factors of reform; the legal system; economic system; publicity right; legal optimism; the consequences of the reform